Noninvasive brain stimulation in psychiatric disorders: a primer - Brunoni,Andre R. (2019)
Objective: Noninvasive brain stimulation (NIBS) techniques, such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), are increasingly being used to treat mental disorders, particularly major depression. The aim of this comprehensive review is to summarize the main advances, limitations, and perspectives of the field. Methods: We searched PubMed and other databases from inception to July 2017 for articles, particularly systematic reviews and meta-analyses, evaluating the use of NIBS in psychiatric disorders. Results: We reviewed the mechanisms of action, safety, tolerability, efficacy, and relevant clinical parameters of NIBS. Repetitive TMS is already an established technique for the treatment of depression, and there is theoretically room for further methodological development towards a high-end therapeutic intervention. In contrast, tDCS is a technically easier method and therefore potentially suitable for wider clinical use. However the evidence of its antidepressant efficacy is less sound, and a recent study found tDCS to be inferior to antidepressant pharmacotherapy. Clinical trials using rTMS for other mental disorders produced mixed findings, whereas tDCS use has not been sufficiently appraised. Conclusion: The most promising results of NIBS have been obtained for depression. These techniques excel in safety and tolerability, although their efficacy still warrants improvement.